2015
DOI: 10.3389/fgene.2015.00126
|View full text |Cite
|
Sign up to set email alerts
|

Small regulatory RNAs in Streptococcus pneumoniae: discovery and biological functions

Abstract: Streptococcus pneumoniae is a prominent human pathogen responsible for many severe diseases and the leading cause of childhood mortality worldwide. The pneumococcus is remarkably adept at colonizing and infecting different niches in the human body, and its adaptation to dynamic host environment is a central aspect of its pathogenesis. In the last decade, increasing findings have evidenced small RNAs (sRNAs) as vital regulators in a number of important processes in bacteria. In S. pneumoniae, a small antisense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Although the pneumococcus expresses a great number of sRNAs with evidence for important physiological roles (Mann et al , ; Laux et al , ; Wilton et al , ), homologs of CsrA, Hfq, or ProQ are not present in this organism (Tettelin et al , ). A preliminary prediction from our cluster analysis and subsequent protein co‐purification experiments is that S. pneumoniae perhaps does not possess a general RBP analogous to Hfq or ProQ, the two RBPs that together associate with > 80% of the sRNAs in E. coli and Salmonella (Holmqvist & Vogel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pneumococcus expresses a great number of sRNAs with evidence for important physiological roles (Mann et al , ; Laux et al , ; Wilton et al , ), homologs of CsrA, Hfq, or ProQ are not present in this organism (Tettelin et al , ). A preliminary prediction from our cluster analysis and subsequent protein co‐purification experiments is that S. pneumoniae perhaps does not possess a general RBP analogous to Hfq or ProQ, the two RBPs that together associate with > 80% of the sRNAs in E. coli and Salmonella (Holmqvist & Vogel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of tmRNA in the pneumococcus was recently demonstrated (Kumar et al, 2010; Acebo et al, 2012; Mann et al, 2012; Wilton et al, 2015) and, although no functional studies have been reported so far, its deficiency has strong effects in pathogenesis. In fact, ssrA inactivation reduced the ability to adhere and to invade endothelial cells, reduced the fitness and competitive index in lungs and causes attenuation in invasive diseases upon intranasal challenge (Mann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because SdbA is required for disulfide bond formation (26), CiaRH might respond to general stress created by misfolding of SdbA substrates or by the loss of function of a specific SdbA substrate. Bacteria sense envelope stress by using two-component systems, and thiol-disulfide oxidoreductases have been linked to these stress responses in both Gram-negative and Gram-positive species (61)(62)(63)(64). For example, Bacillus subtilis senses envelope stress by using a system called CssRS, which, like CiaRH in streptococci, regulates expression of the DegP-family proteases HtrA and HtrB (65,66).…”
Section: Figmentioning
confidence: 99%